2019
DOI: 10.1002/mp.13706
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of 4D‐CBCT reconstructed by Simultaneous Motion Estimation and Image Reconstruction (SMEIR) for carbon ion therapy of lung cancer

Abstract: Purpose Motion management is critical for the efficacy of carbon ion therapy for moving targets such as lung tumors. We evaluated the feasibility of using four‐dimensional cone beam computed tomography (4D‐CBCT) reconstructed by Simultaneous Motion Estimation and Image Reconstruction (SMEIR) for dose calculation and accumulation in carbon ion treatment of lung cancer. Methods Motion‐compensated 4D‐CBCT images were reconstructed with the SMEIR algorithm to capture the most updated anatomy and motion with an upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…A range analysis was not conducted since small differences become extensive in lung tissue, due to its low density. The DVH and gamma analysis results are comparable to those reported by Shrestha et al (2019) for a 4DCBCT carbon-ion lung cancer study, which used simulated projections and a motion-compensated reconstruction algorithm. Furthermore, the DVH analysis and gamma PR showed good agreement to previous 4DvCT studies.…”
Section: Discussionsupporting
confidence: 71%
“…A range analysis was not conducted since small differences become extensive in lung tissue, due to its low density. The DVH and gamma analysis results are comparable to those reported by Shrestha et al (2019) for a 4DCBCT carbon-ion lung cancer study, which used simulated projections and a motion-compensated reconstruction algorithm. Furthermore, the DVH analysis and gamma PR showed good agreement to previous 4DvCT studies.…”
Section: Discussionsupporting
confidence: 71%
“…For example, using four-dimensional cone beam computed tomography (4D-CBCT) reconstructed by simultaneous motion estimation and image reconstruction (SMEIR) can capture the projections of all phases of lungs on the treatment day. Therefore, better treatment planning and dose calculation can be performed for CIRT, and the effect of periodic lung movement on the curative effect will be reduced [83,86,87]. In addition, the Compton camera is capable of detecting 511 keV annihilation gamma rays produced by carbon ion beams interacting with target tissues and is small enough to be easily installed in a treatment room.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown that 4D CBCT offers a more accurate target location as compared to 3D CBCT for motion-involved sites (Kumar et al 2012, Sweeney et al 2012. Furthermore, 4D CBCT has been used to reconstruct and monitor the actual dose delivered to patients for adaptive radiation therapy (Qin et al 2018, Shrestha et al 2019. For 4D CBCT, if single frame 3D reconstruction methods are used, the radiation dose to image the patient would have to increase dramatically to keep the image quality since each of the 3D image series needs a regular scan.…”
Section: Introductionmentioning
confidence: 99%